Prevalence of sleep practices and sleep problems of schoolchildren in South Kanara - Anusha Yerra; Vabitha Shetty (Wolters Kluwer Medknow Publications, 2021)
Background: Disturbances in sleep could affect normal growth as well as behavior of children. It could also impair their cognitive development. Sleep problems have been increasing over the past few years. However, there is a gap regarding information about sleep practices and sleep problems among Indian children. Aim: A sleep questionnaire was designed and validated to assess the frequency of sleep practices and sleep problems in 500 children. Materials and Methods: The study was conducted in 5 local schools in South Kanara district by administering the questionnaire to the parents/caretakers under the guidance of a trained investigator. We also sought to examine the association of demographics, medical/behavior/academic performance, sleep patterns, and home environment to sleep problems in these children. Statistical Analysis: Descriptive statistics were recorded as mean and standard deviation for quantitative data and in frequency and percentage for qualitative data. Results: We found a high prevalence of bedroom sharing (92.4%) and bed-sharing (91.2%). 46.4% of the children exhibited at least one sleep problem, the most prevalent being bed-wetting (17%). Sleep problems were considerably greater in older children and in children with behavioral problems. Practices such as watching TV and using computer after 8 pm/at bedtime were significantly associated with all sleep problems. Conclusion: Our study revealed definite and significant presence of sleep problems in the children of South Kanara. Strong associations were observed between certain sleep practices and problems.